2011
DOI: 10.3945/ajcn.111.012252
|View full text |Cite
|
Sign up to set email alerts
|

Fish intake and type 2 diabetes in Japanese men and women: the Japan Public Health Center–based Prospective Study

Abstract: In a population with high fish and seafood intake, fish consumption was associated with a lower risk of type 2 diabetes in men but not in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 30 publications
1
105
3
Order By: Relevance
“…Our findings are consistent with a number of previous population-based prospective cohort studies on the relationships between fish consumption and n-3 FAs intake on the one hand and T2D prevalence on the other, conducted among different populations (Patel et al 2009;Nanri et al 2011;Villegas et al 2011). Patel et al (2009 reported that consumption of one or more portion of fish per week decreased the OR for diabetes by about 25% compared with less than one portion per week in analyses adjusted for a number of risk factors for diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are consistent with a number of previous population-based prospective cohort studies on the relationships between fish consumption and n-3 FAs intake on the one hand and T2D prevalence on the other, conducted among different populations (Patel et al 2009;Nanri et al 2011;Villegas et al 2011). Patel et al (2009 reported that consumption of one or more portion of fish per week decreased the OR for diabetes by about 25% compared with less than one portion per week in analyses adjusted for a number of risk factors for diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Patel et al (2009 reported that consumption of one or more portion of fish per week decreased the OR for diabetes by about 25% compared with less than one portion per week in analyses adjusted for a number of risk factors for diabetes. Nanri et al (2011) found that fish intake in men was significantly associated with a decreased risk of T2D with the OR values of T2D prevalence for the highest compared with the lowest quartile of intake being 0.73 (95% CI: 0.54-1.00) for total fish intake and 0.68 (95% CI: 0.5-0.92) for small and medium fish. Villegas et al (2011) found that the relative risks for quintiles of fish intake were 1.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our analyses, protein from dairy and protein from cheese were not accountable for the reported reduced type 2 diabetes risk associated with dairy (14-16) and cheese consumption. Fish consumption is not associated with type 2 diabetes (20)(21)(22)(23)39), so possibly our observed association between animal protein and increased type 2 diabetes risk is counterbalanced by potential risk-reducing nutritional components of fish. The findings of this study did not confirm the suggested reduced type 2 diabetes risk associated with protein intake from plant products (especially legumes [18] and nuts [19]).…”
Section: Discussionmentioning
confidence: 88%